A comparison of rectal, oesophageal and gastro‐intestinal tract temperatures during moderate‐intensity cycling in temperate and hot conditions. (2nd September 2014) - Mündel, Toby; Carter, James M.; Wilkinson, David M.; Jones, David A.
Summary: The purpose of this study was to compare three of the most commonly used methods of core temperature ( T core ) measurement during cycling under different environmental conditions as there are practical problems associated with each method and, sometimes, uncertainty as to which is the appropriate measure. Eight trained males ( V ˙ O2 max: 60 ± 7 ml kg −1 min −1 ) completed two 60‐min cycling trials at 70% V ˙ O2 max at 20°C (MOD) and 35°C (HOT). Measures of T core were made every 5 min with oesophageal ( T oes ) and rectal ( T rec ) thermistors and of the gastro‐intestinal tract temperature ( T gi ) with a temperature‐sensitive disposable radio pill. During MOD T oes initially plateaued after 10 min, T gi after 25 min and T rec after 50 min, whereas during HOT these times had increased to 25 min for T oes and 55 min for both T gi and T rec . T oes consistently provided lower readings than T rec (0·24–0·26°C) and T gi (0·26–0·28°C) with T gi and T rec similar (0·02°C). Readings for T gi displayed closer agreement with T rec (ICC = 0·92) than T oes (ICC = 0·86) with less agreement between T rec and T oes (ICC = 0·84). 95% of all T gi readings were within ±0·5°C of T rec and within ±0·6°C of T oes with 95% of all T oes readings being within ±0·7°C of T rec . These results demonstrate distinct response times, absolute values and agreement between T core measured at different body locations under different ambient conditions. Implications and considerations are discussed.